The Role of Taxation in Addressing Inequality A Literature Analysis.docx - Nurwanah, Andi (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to explore the role of taxation in addressing economic inequality, focusing on progressive tax systems and their effectiveness in redistributing wealth and mitigating disparities. Research Design and Methodology: The research employs a qualitative literature analysis, synthesizing insights from seminal works, empirical studies, and cross-country comparisons. Key sources include Piketty's